HOW TEACHERS ADAPT THEIR TEACHING APPROACHES TO DIFFERENT AGE GROUPS - Qodiraliyev Otabek (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This  article  examines  how teachers adapt their teaching  approaches  to  meet  the specific needs and characteristics of different age groups. It  examines  the importance of understanding the developmental  stages,  cognitive abilities, and learning styles of different age groups and how teachers modify their  teaching  strategies accordingly. The article discusses  the   different  methodologies  used  by teachers, examines the implications and benefits of age-appropriate teaching, presents  a  discussion  of  the challenges  teachers   face,  and provides  an   overview   of  the  observed   findings.  The conclusion  emphasizes  the  importance  of  appropriate  teaching methods for optimal learning outcomes and suggests further  areas   for   research.  The article includes a bibliography for  further   reading.